Assessment of Psychophysiological Responses of Drug Addiction Students through HRV Biofeedback - Muhammad Nubli, Abdul Wahab; Salam, Urme (IJMRA, 2014)
Drug addiction is a severe problem to the family, society as well as all over the world which is increasing rapidly especially among the adolescent. Though Malaysia is a peaceful country but it is not an exception of this social disease. Islamic approach such as Salah is the significant stimuli for Muslim, helps to reduce thisproblem. Heart rate variability (HRV) biofeedback is used as a tool for self-regulating physiological conditions to improve the psycho physiological interfaces.HRV biofeedback has been used to measure the psychophysiological responses of the respondents. In this work, 24 male school students were randomly selected from SMK Lepar Hilir, Gambang, Kuantan, Pahang, Malaysia were treated with Salah and HRV biofeedback to change their emotional responses through HRV. The findings of this study depicted that Salah and HRV biofeedback effect significantly change the psychophysiological condition and eventually decrease the addiction behavior of the respondents.